(untitled) (Journal of Parents and Teachers, 2014)
The article shows in a very concise and visual way the structure of the education system in some European countries such as Portugal, France, Germany or Spain. Special attention is also given to the Secondary stage in which the teaching hours, ratios and the principles and main methodologies followed are detailed